Integrable lattice models for strongly correlated electrons - Quinn, Eoin (Trinity College (Dublin, Ireland). School of Mathematics, 2013)
This thesis is dedicated to the study of a new family of integrable lattice models for strongly correlated electrons, namely the Hubbard- Shastry models. The techniques of exactly solvable models, and in particular those of integrable systems, are used. The models are constructed through the quantum inverse scattering method and are studied in one dimension through their Bethe ansatz solution.
Keywords: Mathematics, Ph.D.; Ph.D. Trinity College Dublin